Lessons learned from operationalizing the integration of nutrition-specific and nutrition-sensitive interventions in rural Ethiopia - Girmay Ayana Mersha; Eshetu Zerihun Tariku; Wanzahun Godana Boynito; Meseret Woldeyohaness; Tadese Kebebe; Birhanu Wodajo; Stefaan De Henauw; Souheila Abbeddou (PLoS ONE, 2025)
Background Undernutrition reduction requires coordinated efforts across sectors to address its causes. A multisectoral approach is important in diagnosing the problem and identifying solutions that would be implemented across different sectors. The study aimed to explore the experience of health and agriculture extension workers in integrating nutrition-specific and nutrition-sensitive interventions provided to households with children under two years of age at community level. Methods A qualitative study was conducted in agrarian areas of Ethiopia following the completion of a multi-sectoral program that integrated health and agriculture interventions, in 2021. The program’s goal was to reduce stunting and improve the dietary diversity of young children. In total, 28 key informant interviews were conducted with health- and agriculture-extension workers and mothers. A framework analysis approach was applied to manage and analyze data using NVivo version 12 software. Results The study showed that joint health and agriculture interventions improved community knowledge on childcare and agricultural practices. The practice of farm gardening and cooking demonstrations were improved after the implementation of the program. Because of service integration, extension workers perceived an improved father’s role in supporting mothers in childcaring and feeding nutritious diets to children and decreased severe cases of undernutrition. Integration of health and agriculture sectors for nutrition intervention was challenged by the high workload on extension workers, poor supervision and leadership commitment, lack of appropriate agricultural inputs, and absence of clarity on sector-specific roles. In some areas nutrition services are not owned by the health and agriculture sectors, and it was overlooked. Conclusion Integrating community-level platforms were key entry points to address undernutrition and promote key agriculture and health interventions. The joint implementation of health and agriculture services were effective in the reduction of wasting and improved the role of family members in supporting mothers. However, Integration of sectors were facing challenges in creating shared vision to improve nutrition status of children and women, distributing workload and equal commitment among sectors.